Effect of buffers and supplemental potassium in diets of early-weaned calves - Jordan, K.J.; Morrill, J.L.; Reddy, P.G.; Higgins, James J.; Anderson, N.V. (Kansas Agricultural Experiment Station, 2012)
Potassium chloride added to the prestarter and/or potassium bicarbonate added to the starter fed to early weaned calves helped maintain normal blood alkalinity and normal levels of blood gases, and resulted in a trend toward increased feed consumption. Potassium bicarbonate added to the starter tended to improve weight gains.
Keywords: Dairy; Potassium; Gain; Feed consumption